Rodzice w edukacji – między dyskursem instrumentalno-technicznym a krytyczno-emancypacyjnym - Wiatr , Marta (Studia Edukacyjne, 2019)
This article presents an analysis of discourses on the subject of parental involvement in school education of a child and aims to emphasize the complexity of the topic and the diversity of research positions, as well as further practical implications for the theoretical assumptions adopted. Initial considerations present the terminology functioning in the context of the parent-school relationship. Concepts such as cooperation and partnership (familiar in Poland) have been juxtaposed with English-language concepts engagement and involvement, relating to the participation in the child’s education and/or supporting a child during learning. While English-language terminology stresses the function of this involvement and participation, which is improving the child’s school achievements, the concepts of cooperation and partnership, prevalent in Poland, emphasize the very essence of the relationship and its determinants. In this work, these concepts are presented against the background of the dominant instrumental-technical discourse and a less-emerging but very important critical-emancipatory discourse. Looking at the issue from different sides and analyzing its multifaceted structure allows to broaden the knowledge about the “figure” of a parent who is now emerging in education as a participant in the space of family-school relations.